Granular Rough Theory: A representation semantics oriented theory of roughness - Chen, Bo; Sun, Ming; Zhou, Mingtian (Applied soft computing, 2009)
The present work is an archival paper for a series of contributions proposed in last few years on building a theory of roughness over pure mereological relations among information granules. There are five major efforts taken in the present paper: (1) emphasizing on the representational semantics of theory of roughness: to approximately represent a class of entities characterized by some aspects in terms of entity collections described at other aspects; (2) defining a representation model Granular Representation Calculus (GrRC) to synthesize complex information systems from information granules; (3) establishing notion of Granular Rough Theory (GrRT) over information granules operated in terms of GrRC; (4) extending GrRC/GrRT to various computational environments such as multi-agent systems and ontological computing environments; (5) exploring pragmatic aspects of GrRC/GrRT in implementing prototypes with data model and object programming orientations, and proposing an Ontology-Driven Web Information System as a granular-rough computational Web intelligence framework over GrRC/GrRT.